Moderate alcohol consumption does not protect cognitive function when controlling for income and cultural factors - Gillespie, Kerri M.; Kemps, Eva; White, Melanie J.; Bartlett, Selena E. (Frontiers in Aging Neuroscience, 2025)
IntroductionAlcohol consumption is commonly considered to be a modifiable risk factor in cognitive decline. However, numerous studies have found an association between light to moderate consumption of alcohol and enhanced cognitive function. It has been proposed that this finding is due to the effects of socioeconomic status (SES) or other covariates on drinking behaviors. The present study aimed to investigate the effect of alcohol on cognition, and the impact of different socioeconomic indicators on this relationship.MethodsAn online, cross-sectional survey, including an assessment of five domains of cognitive function, was conducted in 123 healthy adults between 18 and 70 years of age. Secondary analysis of the 2018 National Health Survey was conducted to investigate drinking patterns, and their relationships to SES indicators, in the Australian population.ResultsIncome and education showed dissimilar patterns of association with alcohol consumption. Enhancements in cognitive function were associated with light to moderate dose and frequency of alcohol consumption when unadjusted, or adjusted for SES using education level as an indicator. Benefits of light to moderate dose and frequency of consumption were not evident when using income as an indicator for SES. Inclusion of language spoken in the home as a covariate also resolved any association between moderate consumption and enhanced cognitive function.DiscussionFindings suggest that associations between moderate alcohol consumption and cognition are an artifact of income, language proficiency, and culture. The use of income is more indicative of drinking behavior than education, and should be controlled for in studies of alcohol consumption behavior. Language spoken at home is also an important consideration as this factor is significantly associated with income, alcohol consumption, and cognitive test performance.